2014
DOI: 10.1039/c3sm52354c
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of gel–sol transition in cyclodextrin-based hydrogels as revealed by FTIR-ATR spectroscopy

Abstract: The phase transition from gel to liquid suspension in cyclodextrin (CD)-based hydrogels is in depth monitored by using Fourier transform infrared spectroscopy in attenuated total reflectance geometry. Cyclodextrin nanosponges (CDNS) synthesized by polymerization of CD with the cross-linking agent ethylenediaminetetraacetic dianhydride at different cross-linking agent/CD molar ratios have been left to evolve from gel phase into liquid suspension upon gradual increase of the hydration level. Measurements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(69 citation statements)
references
References 41 publications
8
61
0
Order By: Relevance
“…the gel). 35 This description of swelling phenomena of nanosponges seems to be consistent with the experimental observation [36][37][38] that NS hydrogels undergo the change of their physical state, from a highly viscous gel to a liquid phase, by varying the hydration level or the temperature of the system. Recent HR-MAS NMR experiments 24 revealed that the regime of diffusivity of molecular species in NS hydrogels is modulated both by structural factors (i.e.…”
Section: 40supporting
confidence: 66%
See 3 more Smart Citations
“…the gel). 35 This description of swelling phenomena of nanosponges seems to be consistent with the experimental observation [36][37][38] that NS hydrogels undergo the change of their physical state, from a highly viscous gel to a liquid phase, by varying the hydration level or the temperature of the system. Recent HR-MAS NMR experiments 24 revealed that the regime of diffusivity of molecular species in NS hydrogels is modulated both by structural factors (i.e.…”
Section: 40supporting
confidence: 66%
“…Therefore, the formation of hydrogels by hydration of NS is supposed to occur after the progressive penetration of water molecules inside the hydrophilic pores present in the nanosponge structure. [35][36][37][38] Moreover, the presence in the polymeric structure of NS of a great number of carboxylic groups makes the water sorption steps dependent on the pH of the starting solution, leading to a change in the mesh size of the hydrogel network 2 and in a different swelling ability of the system. For example, by hydrating b-CDPMA14 with Na 2 CO 3 solution of increasing concentration (from 10 to 25% w/w), an enhancement of the swelling capability with respect to neutral H 2 O is clearly observed (see photographs in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was performed on two types of NS, which were obtained by varying during the synthesis the molar ratio of cyclodextrin to the cross-linker. This choice was made on the basis of structural knowledge of the polymeric network of NS 14,15,30 and by considering previous results for the diffusivity of guest molecules inside NS gels. 31 Finally, the analysis of the thermal dependence of dynamical Raman parameters such as the dephasing time can be correlated with the mechanism of the release of Caf from NS hydrogels in response to external stimuli such as variations in temperature.…”
Section: 29mentioning
confidence: 99%